Techno-economic, environmental and risk analysis of a hydrogen airliner family market entry - Huete Anton, Jon (Cranfield University, 2022)
Civil aviation is in a profound transition motivated by the need to reduce its environmental impact. Most civil aviation institutions and stakeholders are now committed to reach net zero by 2050, though there is no feasible path drafted to achieve this goal. Projected energy efficiency improvements, and the use of sustainable aviation fuels could provide a significant reduction in CO₂ emissions, but to reach net zero all emissions should be eliminated or compensated, and none of these solutions achieve the target. Hydrogen as fuel has zero emissions of CO₂ and can address aviation non-CO₂ emissions in an effective manner, to become a true zero emission alternative. Optimising a hydrogen aircraft to match the capabilities and flexibility of the existing narrowbody or the widebody point to point ultra-long-range capacity will take decades. An speculative alternative to expedite the introduction of hydrogen aircraft using existing technology is the focus of this research. A second and third generation of hydrogen aircraft could bring additional benefits in terms of capability and fuel consumption. But the first generation is focused on a swift change. An evaluation of the capabilities achievable with today’s technology and tube and wing configuration is performed. A redesigned double deck aircraft using the A380 as a baseline, with modified wings and engines, and with a variety of tank configurations is investigated as an initial airliner family. It can provide passenger capacities of 388 to 232 with a range of 3,300 nm to 5,600 nm, respectively. Such airliner family could start decarbonising the long-range sector in 15 years. It offers potential to go one-stop to anywhere in the world. A high-capacity version can travel 1,800 nm with 720 passenger is also studied as a solution for high demand city pair traffic. These findings were presented in ISABE 2022 and ICAS 2022 and published in the ISABE special issue of the Aeronautical Journal. The paper ‘Propulsion System Integration for a First-Generation Hydrogen Airliner’ was awarded a Bronze Prize by the RAeS in 2022 and was the 5th most downloaded paper in 2022 in the Aeronautical Journal with 1599 downloads.ii Cryogenic storage is one of the most critical technologies to be addressed. Lightly insulated tanks can extend the range of the aircraft for a given tank volume, but they are unlikely to be used in a first generation due to the need to manage the vented vapour at the airport. Tank architecture and configurations are explored to understand the current and future implications, finding that diameter and dormancy time requirements are the key design parameters that drive the weight of the tank. This work significantly contributed to win three work packages for ATI managed FlyZero project – Tank Design, Fuel System and Combustion consultancy and Advanced Propulsion – where the methods developed in the thesis were adopted. Particularly relevant was the tank weight finally assumed by FlyZero due to the outcomes of this work, which was half the value assumed in most recent studies. A final exploration looks at the emissions that this swift change route could lead to. Complete decarbonization is not achieved until 2080, despite the early introduction in 2035 of the hydrogen airliners. Nevertheless, it provides a decarbonizing solution superior in the long term to other the solutions being explored based on biofuels.
Keywords: Decarbonization; net-zero; long-range; zero-emissions; redesign; tank configuration